Metamaterials: Nanoscaled Metamaterial as an Advanced Heat Pump and Cooling Media (Adv. Mater. Technol. 2/2016). Issue 2 (May 2016) - Levchenko, Igor; Beilis, Isak I.; Keidar, Michael
Abstract : In article 1600008, Igor Levchenko and co‐workers analytically design a novel nanoscaled high‐temperature metamaterial capable of reversal heat transmission, and examine advanced design variants. Performance characteristics of the metamaterial are calculated as functions of geometrical size, temperature ranges, power, and materials used. The future trends in the development of such a metamaterial are also discussed.